(untitled) (Patan Prospective Journal, 2025)
This paper examines problems and challenges faced by the senior citizens due to their health hazards in Nepal. Indeed, Nepal is undergoing swift population ageing: the percentage of individuals aged 60 and above climbed to 10.2% according to the 2021 Census, leading to increased demands on the healthcare system. This document offers a narrative overview of elderly healthcare in Nepal, compiling demographic trends, existing policies and strategies, service provision (such as geriatric units and community programs), prevalent health issues among seniors, deficiencies in service delivery, and suggestions for improvement. Key discoveries indicate (a) a growing population of older adults, (b) acknowledgment in policies (Senior Citizens Act and new geriatric service initiatives) but insufficient large-scale execution, (c) a shortage of adequately trained ecurity, and community-based support. The article concludes with suggestions for policies and programs to enhance elderly care throughout Nepal. Whatever the programs and policies have been launched and implemented across the country do not seem compatible to the requirement of the elderly citizens of the country.